2018
DOI: 10.1371/journal.pone.0207220
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of genotype Cosmopolitan of dengue virus type 2 and genotype III of dengue virus type 3 in Thailand

Abstract: Dengue is a mosquito-borne disease that has spread to over 100 countries. Dengue fever is caused by dengue virus (DENV), which belongs to the Flavivirus genus of the family Flaviviridae. DENV comprises 4 serotypes (DENV-1 to DENV-4), and each serotype is divided into distinct genotypes. Thailand is an endemic area where all 4 serotypes of DENV co-circulate. To understand the current genotype distribution of DENVs in Thailand, we enrolled 100 cases of fever with dengue-like symptoms at the Bamrasnaradura Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 72 publications
14
59
1
Order By: Relevance
“…Several shifts in the predominant DENV-4 genotype lineages occurred in the Philippines between 2004-2016. In concurrence with other studies in which genotype and lineage turnover coincide with changes in epidemic activity (19,(35)(36)(37)(38), our study demonstrated an increase in the number of DENV-4 patients during the turnover period. While the GIIa lineage in the Philippines forms a distinct lineage, processes of genotype replacement may have been a result of introductory strains and after that on-going local evolution, with the dominance of lineage L3 from the replacement of lineage L2 and sub-lineages within L3 (L3-1-1b).…”
Section: Discussionsupporting
confidence: 92%
“…Several shifts in the predominant DENV-4 genotype lineages occurred in the Philippines between 2004-2016. In concurrence with other studies in which genotype and lineage turnover coincide with changes in epidemic activity (19,(35)(36)(37)(38), our study demonstrated an increase in the number of DENV-4 patients during the turnover period. While the GIIa lineage in the Philippines forms a distinct lineage, processes of genotype replacement may have been a result of introductory strains and after that on-going local evolution, with the dominance of lineage L3 from the replacement of lineage L2 and sub-lineages within L3 (L3-1-1b).…”
Section: Discussionsupporting
confidence: 92%
“…aegypti females caught in 2018 (MN527287-MN527289) were DENV-1 (nucleotide sequence identity > 96%, Figure 2). They were closely related to DENV-1 (LC410183.1) and DENV-4 (LC410203.1) detected in patients from Thailand reported in 2017 [14]. The sequence alignment is shown in Supplementary Figure S2.…”
Section: Phylogenetic Relationship Of Denvmentioning
confidence: 63%
“…Recently, more than 72,000 dengue cases with a fatality rate of 0.13% were reported in 2018 to the Ministry of Public Health, Thailand. All four DENV serotypes (DENV-1, DENV-2, DENV-3 and DENV-4) are reported to circulate in Thailand with a recurrent circulation of each serotype [12,14,15]. The Department of Disease Control-part of the Ministry of Public Health (MOPH), Thailand-reported that the major DENV serotypes causing illness in 2017 were DENV-1 and DENV-4.…”
Section: Introductionmentioning
confidence: 99%
“…DENV-2 Cosmopolitan genotype was first reported in 1944 in Papua New Guinea and Indonesia (7), and the emergence of DENV-2 Cosmopolitan genotype is widely observed in some countries, such as Pakistan and Thailand (8,9). As DENV-2 serotype is associated with severe dengue infection (10), its international spread could be a menace for global health.…”
Section: Discussionmentioning
confidence: 99%